Characterization and corrosion behaviours of AISI 316 in hydrochloric environment at various concentrations - Sani Adams Mohammed; Clifford Ogheneme Ogheneblorhie (Zaštita Materijala, 2020)
Characterization and corrosion behaviours of austenitic stainless steel (AISI 316) types at various concentrations of hydrochloric acid solutions were investigated in relation to its pitting corrosion resistance. Both gravimetric-weight loss and potentiodynamic polarization were used for the investigations. The AISI 316 was characterized by X-ray fluorescent (XRF). The characterization of the coupon before and after the corrosion test in various concentrations was done using scanning electron microscopy (SEM). The temperature, acid concentration and time were varied in the range of 30-60°C at 10°C interval, 0.5-2M at 0.5M interval and 1 to 6 day at 1 day interval, respectively. The XRF revealed some important elements in the AISI 316 such as (Cr, Ni, Mn, Si, C, S, P etc) which confirmed the materials to AISI 316. The weight loss results revealed that the corrosion rate decreased with increase in exposure time from day 1 to day 6. The corrosion rate of the AISI 316 increased with increase in temperature, severe to pits formation and growths with increase in concentration of acid from 0.5 - 2M. The corrosion rate of AISI 316 increases with increase in acid concentrations. The Tafel results also revealed that both anodic and cathodic sites were shifted with the lowest corrosion resistance occurring at 0.5M of HCl. The SEM of the coupons in the presence of acid revealed pits formation, growths and pitted AISI 316 surfaces. The results obtained from the weight loss, Tafel and characterization were also in good agreement.